Effect of oocyte with CLCG on embryo development and implantation rates after ICSI In Freeze-Thaw Embryo Transfer Cycles. - Raghunandan, K.; Chandan, N.; Rajeshwari, P.; Somana, Harshitha; Harsha, H.C. (International Journal of Scientific Research in Biological Sciences, 2021)
Introduction: Oocyte quality plays a major role in understanding the fertility potential of the female, which is primarily reflected by oocytes and their morphological features. A type of cytoplasmic abnormality exhibited by oocytes that can affect the oocyte quality is Centrally located cytoplasmic granulation (CLCG). Morphological variations of the oocyte may result due to different factors. Aim: To evaluate the consequences of CLCG on embryo development and implantation rates after ICSI in Freeze-Thaw Cycles. Methods: It was a retrospective study. A total of 418 day3 and 157 day5 patients who had undergone frozen-thawed cycles were recruited. Patients who had embryo transfer with CLCG were grouped as Test group (n = 100, n=90 day3 and n=38, n=42 day5. As per age <30 and age >31) and patients who had embryo transfer with normal oocytes morphology were grouped as the control group (n = 125, n=103 day3 and n=33, n=44 day5. As per age <30 and age >31) respectively. Results: Among the CLCG and the control group, there was no significant difference observed in the patient`s age, FSH, LH, and AMH. However, the maturation and fertilization rate among the patients age >31(P <0.05) years had a significant difference, and we also inferred that the CLCG did not affect the embryo development and implantation rate (P >0.05) in both groups respectively (age <30 and age >31). Conclusion: These results suggested CLCG might be a normal morphology of oocytes. There was no significant difference in embryo development patients with or without CLCG. The patients who freeze-thawed transferred CLCG embryos had a successful outcome.